2022
DOI: 10.1155/2022/9222541
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Fisetin on Allergic Contact Dermatitis via Regulating the Balance of Th17/Treg in Mice

Abstract: Background. Allergic contact dermatitis (ACD) is a form of chronic cutaneous inflammatory disease of immunological origin that has adverse impacts on patient quality of life, underscoring the need for the development of safe and effective therapeutic agents to treat affected individuals. Fisetin is a Chinese herbal preparation that reportedly exhibits antitumor, antioxidant, antimicrobial, anticoagulatory, and antimalarial activity. In the current report, the immunomodulatory activity of fisetin was appraised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…8 F). The results indicated that although the IL-10 level was decreased in chondrocytes stimulated with IL-1β compared with the untreated group (control group), the treatment with FNPs, like fisetin 48 , 49 , increased its level in IL-1β pretreated human chondrocytes. In general, these results showed that FNPs can inhibit the inflammatory responses induced by IL-1β, including the expression of TNF-α, and IL-6, and reduce the degradation of Sox-9, COL2, and SirT1 in OA chondrocyte cells.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…8 F). The results indicated that although the IL-10 level was decreased in chondrocytes stimulated with IL-1β compared with the untreated group (control group), the treatment with FNPs, like fisetin 48 , 49 , increased its level in IL-1β pretreated human chondrocytes. In general, these results showed that FNPs can inhibit the inflammatory responses induced by IL-1β, including the expression of TNF-α, and IL-6, and reduce the degradation of Sox-9, COL2, and SirT1 in OA chondrocyte cells.…”
Section: Resultsmentioning
confidence: 90%
“…However, similar to fisetin, FNPs reduced TNF-α and IL-6 mRNA expression in IL-1β stimulated cells. Next, the effect of FNPs on the mRNA expression of IL-10, a well-known anti-inflammatory cytokine 48 , 49 , was investigated in IL-1β stimulated human chondrocytes (Fig. 8 F).…”
Section: Resultsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%